Studi luas genangan banjir pada suatu das yang memiliki bangunan tanggul(study kasus das way pisang) - LIDYANA PUTERI (Civil Infrastructure Engineering and Architectural Design, 2023)
Abstract: Way Pisang is a river in south Lampung Regency – Lampung, that potentially flooding every year, crossing the Penengahan, Palas and Sragi Districts. The floods that occur almost every year, has an impact on the moral and material losses to the residents who lived around the location.Flood prevention around the Way Pisang river is done by adding some embankments for its rehabilitation. The simulations of the embankment infrastructure existed carried out using HEC-RAS software. This simulations were carried out at certain locations that profiled potentially welled up at B.34 to A.76 or Sta. 01 to 109.From its modeling, resulting that the existence of an embankment with a high puddle area in year 2007, for Q10 are 270/Ha and for Q25 are 330/Ha. Furthermore, flood inundation area flooded in year 2015 was 310/Ha for Q10 and 340/Ha for Q25.Keywords: Way Pisang, Embankment and HEC-RAS.